Botulinum Toxin Type A Possibly Affects Cav3.2 Calcium Channel Subunit in Rats with Spinal Cord Injury-Induced Muscle Spasticity - Ma K; Zhu D; Zhang C; Lv L (Dove Medical Press, 2020)
Kening Ma,1 Dan Zhu,2 Chunguo Zhang,1 Lijie Lv3 1Department of Pain Medicine, The First Hospital of Jilin University, Changchun 130021, People’s Republic of China; 2Department of Neurologic Medicine, The First Hospital of Jilin University, Changchun 130021, People’s Republic of China; 3Department of Medicine and Pension, The First Hospital of Jilin University, Changchun 130021, People’s Republic of ChinaCorrespondence: Lijie LvDepartment of Medicine and Pension, The First Hospital of Jilin University, No. 71 Xinmin Street, Changchun 130021, People’s Republic of ChinaTel +86-431-88782032Email lvlj1010@126.comIntroduction: Spinal cord injury (SCI) often causes muscle spasticity, which can be inhibited by using calcium channel blocker. Botulinum toxin type A (BoT-A) shows therapeutic efficacy on spasticity and may exert inhibitory effects on the calcium channel.Methods: A rat model with muscle spasticity was established after SCI via contusion and compression. Different concentrations (0, 1, 3 and 6 U/kg) of BoT-A Botox were injected in the extensor digitorum longus (EDL) muscles of the right hindlimb in the muscle spasticity model. The changes of muscle spasticity and calcium level in EDL muscles were measured after the establishment of SCI-induced spasticity. Cav 3.2 calcium channel subunit and its mutant (M1560V) were analyzed using Western blot before (input) or after immunoprecipitation with anti-FLAG antibody, and their currents were measured in motoneurons by using whole-cell voltage clamp recordings.Results: SCI induced muscle spasticity, whereas calcium level in EDL muscles and expression of Cav 3.2 was increased in the SCI model when compared with the sham group (p < 0.05). BoT-A Botox treatment significantly reduced muscle spasticity and calcium level in EDL muscles and Cav 3.2 expression in a dose-dependent way (p < 0.05). The ratio of biotinylated to total Cav 3.2 was reduced in the mutant (M1560V) of Cav 3.2 and lower than that in the wild Cav 3.2. BoT-A Botox intervention also reduced the current values of calcium channel and the ratio in a dose-dependent way (p < 0.05).Discussion: BoT-A Botox possibly attenuates SCI-induced muscle spasticity by affecting the expression of Cav 3.2 calcium channel subunit in the rat models. There may be multiple mechanisms for the function of BoT-A Botox. Further work is needed to be done to address these issues.Keywords: botulinum toxin type A, muscle spasticity, Cav 3.2 calcium channel, rat model, spinal cord injuries